Tafsir Al-Misbah dan Al-Maraghi Tentang Nilai-nilai Pendidikan yang Tekandung dalam Surat Al-Kahfi ayat 66-70 (Tafsir al-muqarin Tafsir Tafsir Al-Misbah & Al-Maraghi) - Muhammad Zainal Abidin (STAI Terpadu Yogyakarta, 2021)
Al-Qur'an as a guide to Muslim thought provides many lessons that need to be developed philosophically and scientifically, as a framework for building Islamic education. One of the methods used by the Koran to provide a journey for humans is by describing the stories that exist in the Koran itself. This research is a research library research using the Muqarin (comparative) method in its analysis. The results of the research analysis show 1) Interpretation of M. Quraish Shihab and interpretation of Ahmad Mustafa Al-Maraghi. Quraish uses the method of writing tahlili and maudhi (thematic) interpretations and explains the content in the verse with a beautiful editorial then pays attention to vocabulary or language to highlight the Koran in human life, explaining the contents of the verse one by one first then globally reviewed the contents of the letter in general. While Al-Maraghi uses the tahlili method which is based on a combination of bi al-ma'sur and bi al-ra'yi, by explaining in detail the incidents and events per verse. In the interpretation of Al-Maraghi, he often connects events or words in the verse logically so that the story in the verse seems logical and sequential. 2) The values of education in general are about the command to study until the end of life, so that mankind does not have an arrogant character to learn from anyone and does not fast fast when gaining knowledge. Educational values for teachers about how to implement good teaching strategies and characteristics that an educator or teacher must have, such as being patient, forgiving when students make mistakes, making him a worthy person to be imitated. Then the educational values for students about morals for teachers must be curious, polite, unyielding and willing to learn from anyone regardless of rank and degree